2006
DOI: 10.1680/macr.2006.58.8.489
|View full text |Cite
|
Sign up to set email alerts
|

Gas permeability measurements of cement-based materials under hydrostatic test conditions using a low-transient method

Abstract: Argon permeability of a mortar, made with a water/cement ratio of 0 . 4, was measured cyclically as a function of confining pressure up to ó 3 ¼ À57 MPa. An original low-transient method was used, in which the time required to observe a slight gas pressure decay is measured. The mechanical behaviour and hydraulic response were both studied. The mortar seems crack-free and isotropic. It behaves elastically, even if a significant hysteresis, ascribed here to some microsliding between the C-S-H sheets and the mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Gas permeability experiments have been used as an indirect measure to evaluate the durability of cementitious materials [13,14,15,16]. Because of the high penetration resistance of the cementitious material, the experiment proceeds very slowly under natural conditions, and therefore, experiments are usually carried out using high-pressure gas as a medium.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gas permeability experiments have been used as an indirect measure to evaluate the durability of cementitious materials [13,14,15,16]. Because of the high penetration resistance of the cementitious material, the experiment proceeds very slowly under natural conditions, and therefore, experiments are usually carried out using high-pressure gas as a medium.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experimental study of Zhu and Wong [18] on Berea and Boise sandstones resulted in a variable α which increases when pressure increases. Meziani [19] performed an experimental study on the gas permeability of mortar under hydrostatic loading and found a strongly non-linear permeability-porosity relationship. The exponent α is found to be a decreasing function of the loading level, decreasing from 36 to 26 when the confining pressure is increased up to 57 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…The permeability of cement-based materials is one of the most important indicators of long-term durability [17,18], and the transport of internal material is closely related to changes in the pore structure [19][20][21]. There are many methods for measuring the permeability of cement-based materials [22][23][24][25][26], and among them, the gas permeability test method is easy to operate and has high accuracy [27]. Under the coupled activity of dry-wet cycles and sulfate attack, the morphology of the internal pore structure and the connectivity of the pore diameters of cement-based materials change gradually, and this method can reflect the characteristics of the connected pore structure and microcrack changes more sensitively.…”
Section: Introductionmentioning
confidence: 99%